Cannabinoid and substance relationships of European congenital anomaly patterns: a space-time panel regression and causal inferential study. Issue 1 (3rd February 2022) - Reece, Albert Stuart; Hulse, Gary Kenneth
Abstract: With reports from Australia, Canada, USA, Hawaii and Colorado documenting a link between cannabis and congenital anomalies (CAs), this relationship was investigated in Europe. Data on 90 CAs were accessed from Eurocat. Tobacco and alcohol consumption and median household income data were from the World Bank. Amphetamine, cocaine and last month and daily use of cannabis from the European Monitoring Centre for Drugs and Drug Addiction. Cannabis herb and resin Δ9-tetrahydrocannabinol concentrations were from published reports. Data were processed in R. Twelve thousand three hundred sixty CA rates were sourced across 16 nations of Europe. Nations with a higher or increasing rate of daily cannabis use had a 71.77% higher median CA rates than others [median ± interquartile range 2.13 (0.59, 6.30) v. 1.24 (0.15, 5.14)/10 000 live births ( P  = 4.74 × 10 −17 ; minimum E -value (mEV) = 1.52]. Eighty-nine out of 90 CAs in bivariate association and 74/90 CAs in additive panel inverse probability weighted space-time regression were cannabis related. In inverse probability weighted interactive panel models lagged to zero, two, four and six years, 76, 31, 50 and 29 CAs had elevated mEVs (< 2.46 × 10 39 ) for cannabis metrics. Cardiovascular, central nervous, gastrointestinal, genital, uronephrology, limb, face and chromosomalgenetic systems along with the multisystem VACTERL syndrome were particularly vulnerable targets. Data reveal that cannabis is related to many CAs and fulfil epidemiological criteria of causality. The triple convergence of rising cannabis use prevalence, intensity of daily use and Δ9-tetrahydrocannabinol concentration in herb and resin is powerfully implicated as a primary driver of European teratogenicity, confirming results from elsewhere.